Public Conduct In The Implementation Of The Protocol Health During The Covid-19 Pandemic In The Tolitoli Area - Suasa, Suasa; Mukarramah, Mukarramah; Royfandi, Moh.; Alfiandi, Moh. Adrian (Technium Social Sciences Journal, 2023)
This research is related to public behavior in implementing health protocols during the Covid-19 pandemic in Toli-Toli Regency. Aims to find out how the public behaves in the application of health protocols. The method used is descriptive qualitative. Data collection techniques through three stages, namely, observation, then interviews, and documentation. The results of the study indicate that the knowledge aspect is well implemented from the government related to providing education or outreach directly and indirectly to the community related to the dangers of Covid-19 disease. In the Sikpa aspect, it is not in line with the knowledge aspect, where the community is largely ignorant of the application of health protocols. This attitude of indifference or disobedience greatly affects the health protocol policies that have been instructed by the government. This is in line with the last aspect, namely Action, in the previous aspect, namely the attitude that has shown a community response that is indifferent to the application of health protocols and by itself the musty actions are not carried out as expected. Based on the results of the research above, the researchers concluded that the lack of public awareness of the importance of maintaining health and avoiding the deadly disease Covid-19 in Toli-Toli Regency.